Crowded airwaves : campaign advertising in elections - Thurber, James A., 1943-; Nelson, Candice J., 1949-; Dulio, David A. (Brookings Institution Press, 2000)
"Crowded Airwaves gathers some of the most significant new work in American political advertising and communication. The contributors provide an objective and balanced analysis of political advertising: its causes, its growth, and its consequences on elections in the United States." "The chapters in this volume tackle three of the most interesting and most complicated issues in political advertising today: the characterization of ads and the need to measure their impact; the agenda-setting and priming effects of ads; and the role and implications of issue advertising for the electorate. The contributors focus in particular on the effects and consequences of negative advertising." "Crowded Airwaves will appeal to readers who are interested in political campaigns and communication. It will be of special importance to those concerned with the tone and content of electoral campaigns and political discourse."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved